Review of post-traumatic stress disorder related to COVID-19: the need of preventive intervention - Boshra Hatef; Fahimeh Ghahvehchi-Hosseini; Gila Pirzad Jahromi (فصلنامه ابن سینا)
This paper has not the abstract. This paper has not the abstract. This paper has not the abstract. This paper has not the abstract.